Pengaruh Penggunaan CDI Standar Dan CDI Digital Terhadap Daya Dan Torsi Motor Bensin 250CC - Muhamad Nur Fauzi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2023)
As with the engine ignition system, the spark produced by the manufacturer's standard CDI is limited or known as a CDI limiter, in contrast to non-limiter CDI which has no limits or has a higher spark limit on the engine so that it can produce engine performance up to a higher RPM. higher and produces maximum engine performance. Weaknesses in the factory standard CDI can be overcome by replacing it with a racing CDI. Racing CDI has the same quality or even better than standard CDI. Racing CDIs are made by local manufacturers and from abroad and are now easily available in spare parts stores or motorbike repair shops throughout Indonesia.